Pengaruh Kualitas Pelayaan Dan Product Knowledge Terhadap Keputusan Pembelian Customer Yang Dimoderasi Oleh Tingkat Penjualan - Koerniawan Hidajat; Safitri Diandaru (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2020)
This study aims to analyze the effect of service quality, product knowledge and level of sales on purchasing decisions in Indonesia. Population The study was conducted at 17 August University Students in Jakarta. While the samples in this study were students who often shopped. In this study using Random Sampling, which is anyone who met the author can be sampled. Data collection is done by providing a list of questions to respondents and tested using the validatasion and reliability test analysis method using smartPLS. The purpose of this study is to determine how much influence between purchasing decisions and product knowledge on purchasing decisions moderated by the level of sales. Based on the results of this study it can be concluded that the influence of service quality on purchasing decisions (X1 to Y) and the effect of product knowledge on purchasing decisions (X2 to Y) and moderation of the sales level on the influence of product knowledge on purchasing decisions (X2 moderation on Y) produce a significant influence not significant or negative effect because of the T-statistic <1.96 or P Value> 0.05. As for the influence of purchasing decisions on sales (Y to Z), the relationship of product knowledge to the influence of sales levels (X2 to Z) results in a significant or positive effect where T-statistics> 1.96 or P Value <0.05.Keywords: service quality, product knowledge and level of sales